Accounting for the invisible value of trees on farms through valuation of ecosystem services - Chiputwa, Brian; Ihli, H.; Wainana, P.; Gassner, A. (Elsevier, 2020)
The integration of trees on farms, commonly referred to as agroforestry, has been recognized as a potential strategy to enhance farmers' adaptation to and mitigation of the adverse effects of climate change. Agroforestry is also considered as contributor to sustainable food systems. Due to the complexity of agroforestry systems, their contribution to sustainable food systems is often underestimated as some of the goods and ecosystem services (ESs) provided are not traded in official markets. There is an increasing interest among researchers in trying to measure, model, and value ESs overall and the benefits derived from agroforestry specifically. This chapter reviews available tools that can be applied to value both marketed and nonmarketed goods and ESs from agroforestry. Providing decision-makers with improved value estimates that account for the full value of trees on farms is an important step in ensuring better and more targeted policies that promote biodiversity conservation for more sustainable food systems.